A novel therapeutic strategy for non-muscle invasive bladder cancer: OncoTherad® immunotherapy associated with platelet-rich plasma - Ribeiro de Souza, Bianca; Brum Reis, Ianny [UNESP]; Cardoso de Arruda Camargo, Gabriela; Oliveira, Gabriela; Cristina Dias, Queila; Durán, Nelson; José Fávaro, Wagner (Elsevier, 2023)
Patients with non-muscle invasive bladder cancer (NMIBC) that are unresponsive to Bacillus Calmette-Guérin (BCG) have historically had limited treatment options. A new perspective is represented by OncoTherad® (MRB-CFI-1) immunotherapy, a nanostructured inorganic phosphate complex associated with glycosidic protein, developed by the University of Campinas in Brazil. Previous studies have shown that Platelet-Rich Plasma (PRP) also acts on immune activation and exerts antitumor effects. This study characterized the effects of the OncoTherad® associated with PRP in the treatment of NMIBC chemically induced in mice. When treated intravesically with PRP only, mice showed 28.6% of tumor progression inhibition rate; with OncoTherad® 85.7%; and with OncoTherad®+PRP 71.4%. Intravesical treatments led to distinct activation of Toll-like Receptors (TLRs) 2 and 4-mediated innate immune system in the interleukins (canonical) and interferons (non-canonical) signaling pathways. OncoTherad® isolated or associated with PRP upregulated TLR4 and its downstream cascade mediators as well as increased interleukins 6 (IL-6) and 1β (IL-1β), and interferon-γ (IFN-γ). In this way, the NMIBC microenvironment was modulated to a cytotoxic profile correlated with the IL-1β increase by stimulating immune pathways for IFN-γ production and consequent cytotoxic T lymphocytes (as CD8+ T-cells) activation and regulatory T-cells (Tregs) reduction. In addition, PRP did not trigger carcinogenic effects through the biomarkers evaluated. Considering the possibility of personalizing the treatment with the PRP use as well as the antitumor properties of OncoTherad®, we highlight this association as a potential new therapeutic strategy for NMIBC, mainly in cases of relapse and/or resistance to BCG.
Keywords: Bladder cancer; Immunotherapy; OncoTherad; PRP; Toll-Like receptors